Comparative Study of Conventional and Microwave-Assisted Boriding of AISI 1040 and AISI 4140 Steels - Safiye İpek Ayvaz; Emre Özer (Tehnički Glasnik, 2023)
In this study, AISI 1040 and AISI 4140 steels were boriding using Ekabor-II commercial boriding powder with powder-pack boriding method using microwave and conventional heating methods. The samples were borided at 950 °C for 2 and 6 hours in an Ar atmosphere in a microwave oven of Enerzi-Mh2912-V8. Biphasic structure (FeB/Fe2B) was formed in all borided AISI 4140 samples and AISI 1040 samples borided for 6 hours. A single-phase structure was observed in AISI 1040 steel borided for 2 hours. Compared to the conventional method, a 1.5-1.6 times thicker boride layer was obtained in AISI 4140 and AISI 1040 steels with microwave-assisted powder-pack boriding. The highest hardness was measured as 1561.8 HV0.05 for boriding AISI 4140 steel and 1499.7 HV0.05 for boriding AISI 1040 steel. The Vickers indentation fracture toughness of borided steels with microwave energy varied between 2.31 and 3.46 MPa·m1/2. It was determined that in all samples borided by the microwave-assisted and conventional powder-pack boriding method, the adhesion strength between the boride layers and the substrate obtained was sufficient.